2006
DOI: 10.1210/en.2005-1624
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Insulin Sensitivity after Peroxisome Proliferator-Activated Receptor-α Agonist Treatment Is Accompanied by Paradoxical Increase of Circulating Resistin Levels

Abstract: We studied the effect of peroxisome proliferator-activated receptor-alpha (PPAR-alpha) activation on serum concentrations and tissue expression of resistin, adiponectin, and adiponectin receptor-1 and -2 (AdipoR1 and AdipoR2) mRNA in normal mice and mice with insulin resistance induced by lipogenic, simple-carbohydrate diet (LD). Sixteen weeks of LD feeding induced obesity with liver steatosis and increased insulin levels but did not significantly affect circulating adiponectin or resistin. Treatment with PPAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 44 publications
4
31
1
1
Order By: Relevance
“…The key distinction between our protocol and that of others is that we use an arterial catheter for obtaining blood samples. This is in contrast to the more widely used approach of obtaining blood samples by severing the tip of the tail 4,7,11,12,[14][15][16][17] . The advantage of sampling from an arterial catheter is that the experiment is conducted in a conscious and unrestrained mouse.…”
Section: Discussionmentioning
confidence: 93%
“…The key distinction between our protocol and that of others is that we use an arterial catheter for obtaining blood samples. This is in contrast to the more widely used approach of obtaining blood samples by severing the tip of the tail 4,7,11,12,[14][15][16][17] . The advantage of sampling from an arterial catheter is that the experiment is conducted in a conscious and unrestrained mouse.…”
Section: Discussionmentioning
confidence: 93%
“…Rossi et al reported that shifting the source of fat to fish oil for 2 months increased plasma levels of both leptin and adiponectin in rats 25) . Haluzik et al reported that fenofibrate treatment did not increase serum adiponectin in mice fed a carbohydrate diet 26) . This is also consistent with our previous observation using C57BL/6J mice that plasma adiponectin increased significantly in fish oil groups, but not in the fish oil with fenofibrate group.…”
Section: Discussionmentioning
confidence: 99%
“…Blood glucose concentrations were monitored at 10-min intervals throughout the clamp studies. Basal and clamp hepatic glucose production (HGP), glucose disposal rate (GDR), and glucose infusion rate (GIR) were calculated as described previously [13].…”
Section: Observation and Assessmentmentioning
confidence: 99%